PENAMBAHAN SALAK JAWA SEBAGAI UPAYA MENINGKATKAN KUALITAS JENANG SALAK PONDOH - Hidayati, Nurul (Politeknik Pembangunan Pertanian Yogyakarta-Magelang, 2011)
This research of Salak Jawa addition as an effort to increase quality of Jenang (toffee-like sweets) Selak Pondoh aimed to find quality of jenang salak pondoh in different rattos of salak pondoh, salak jawa, and sugar. This research r.rsed Completely Randomized Design (CRD). Treatments consisted of two factors, ratio of salak pondoh to salak Jawa and ratio of sugar to salak in the mixtures. Factor of ratios between salak pondoh and salak Jawa consisted of 5 levels: Level I = 0:4, Level II = 1:3, Level III = 2:2,Level IV:3:1 and Level V:4:0. Factor of ratio between sugar and salak consisted of three levels: Level I: l:5, Level II :2:5 and Level II:3:5. In this experiment, the total replications were three replications. Parameters observed were chemical, physical and sensory characteristics. Chemical characteristic included contents of water, total sugar and tannin. Sensory characteristic included texture, taste, color, and preference, tested by Ranking Test type. If there was a real difference, Duncan's real difference test (DMRT) was conducted with confidence interval of 5Yo. The obtainable results of research indicated that the ratio between usable salak pondoh and salak Jawa and the ratio between usable sugar and salak had real effect on chemical characteristics (contents of water, total sugar and tannin) and physical characteristic (texture) of jenang salak and sensory characteristics (taste, texture, and color of jenang salak and preference of consumers to jenang salak). Based on consumers' preference level, good jenang salak was made of salak jawa without the addition of salak pondoh, and ratio between sugar and salak was l:5. The jenang salak had brown-yellow color, medium size texture, not too sweet, and having astringent taste because it contained high tannin.